Peran Pendamping Persalinan dengan Lama Persalinan Kala II di Puskesmas Ranomuuut Kota Manado - Pritty Natasya Latampung; Endang Puji Ati; Meinita Wulansari (Universitas Pahlawan Tuanku Tambusai, 2026)
Childbirth companion Childbirth companion is a supporting factor in the smoothness of childbirth, because the effect of women's feelings towards different childbirths is related to their perceptions of supportive people, from those closest to them can affect maternal anxiety Definition of Childbirth companion Childbirth companion is a supporting factor in the smoothness of childbirth, because the effect of women's feelings towards different childbirths is related to their perceptions of supportive people, from those closest to them can affect maternal anxiety. This study aims to determine the relationship between the role of companions and the length of the second stage of labor in mothers giving birth at the Ranomuut Community Health Center in Manado City. This type of research uses quantitative research with a descriptive correlational approach. The population is 156 mothers giving birth, the sample in this study uses Purposive Sampling where researchers identify relationships or causes of a phenomenon without intervening. The results of the study show that the role of companions who do not play a role is 11 people or 34.4% and the role of companions who play a role is 21 people or 65.6%. Furthermore, data processing and analysis p value 0.001 where P <α 0.05 so that H0 is rejected and Ha is accepted. This means there is a relationship between the role of birth companions and the duration of second stage labor at Ranomuut Community Health Center, Manado City.